(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The socio-economic development of any country directly depends on the efficiency of the use of the labor potential of the population. This means that the effective implementation of market relations in the country, employment and, consequently, the achievement of sustainable socio-economic development will depend, first of all, on the effective use of the existing labor potential of the population. Because the labor potential of the population is a key factor in production, it also has a number of unique features compared to other resources.